Household Welfare Effects of Low-cost Land Certification in Ethiopia - Stein T. Holden; Hosaena Ghebru (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
Several studies have shown that the land registration and certification reform in Ethiopia has been implemented at an impressive speed, at a low-cost, and with significant impacts on investment, land productivity, and land rental market activity. This study provides new evidence on land productivity changes for rented land and on the welfare effects of the reform. The study draws on a unique household panel, covering the period up to eight years after the implementation of the reform. We find that land productivity after the reform has increased more on rented plots with female landlords as compared to male landlords indicating that, particularly, female landlords' land rights have been strengthened. Furthermore, real household consumption expenditures per adult equivalent have increased with the duration of land certificate ownership, most significantly so for female owners of land certificates
Keywords: Q15; 330; Land registration and certification; land rental market participation; land; productivity; welfare impact; gender; Ethiopia